2017
DOI: 10.31235/osf.io/mkarq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Process-Based Ideology of Participative Experimentation to Foster Identity-Challenging Innovations: the Case of Gmail and Adsense

Abstract: Prior research has examined how organizational identity can enable and constrain innovations. A complementaryliterature has examined organizational ideology as the basis for actions driving identity-enhancing innovations.We examine how organizational ideology can serve as the basis for identity-challenging innovations throughan in-depth study of the emergence of two innovations at Google—Gmail and AdSense. Findings from thisstudy highlight a process-based ideology of participative experimentation. We explicate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Processes of experimentation provide a fertile ground to investigate this phenomenon, as they engage organizational members in practices that might be linked to organizational identity work. For example, Garud and Karunakaran (2017) found that participative experimentation can foster identity-challenging innovations. This process is enabled by mechanisms that integrate thinking with doing, the materialization of ideas and collective engagement; thus, there are social, material, and cognitive aspects shaping how organizations foster identity-challenging innovations.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Processes of experimentation provide a fertile ground to investigate this phenomenon, as they engage organizational members in practices that might be linked to organizational identity work. For example, Garud and Karunakaran (2017) found that participative experimentation can foster identity-challenging innovations. This process is enabled by mechanisms that integrate thinking with doing, the materialization of ideas and collective engagement; thus, there are social, material, and cognitive aspects shaping how organizations foster identity-challenging innovations.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…The centrality of experimentation led researchers to identify specific “experimental spaces,” which consist of “transitory social settings where field actors experiment with alternative action models” (Cartel et al, 2019: 3), and to link these experimental spaces to experimentation processes in and around organizations (Bucher and Langley, 2016; Cartel et al, 2019; Garud and Karunakaran, 2017). Some strands of this literature have noted the generative potential of spaces in creating novelty at the organizational and institutional levels (Bucher and Langley, 2016; Hardy and Maguire, 2010; Kellogg, 2009; Zietsma and Lawrence, 2010).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, 3M cultivated Kairos through its 15% "bootlegging rule", which allowed employees to use a portion of their work time to explore their own ideas, to develop a number of new products including a new kind of abrasive (Trizact) that disrupted its existing abrasive product (Garud et al, 2011). Similarly, as the disruptor, Google too cultivated Kairos through its 20% time for participative experimentation to disrupt existing email platforms with its Gmail platform (Garud and Karunakaran, 2018; see also Dougherty, 2016).…”
Section: A Temporal Perspective On Disruptionmentioning
confidence: 99%